Penerapan Pendekatan Whole Language Dalam Pengajaran Literasi Anak Usia Dini - Mutiara, Mutiara Rohmah Dhiny (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study aims to cover the application of the Whole language approach in teaching early childhood literacy. The Whole language approach emphasizes understanding the entire language through reading, writing, listening and speaking activities. This research uses a qualitative approach with a case study approach. The research subjects consisted of a group of early childhood who attended an educational program with the application of the Whole language approach. Data was collected through class observations, interviews with teachers, and observations of children’s literacy development. Data analysis was carried out using an inductive approach, in which the thematic patterns and meanings that emerged from the data were found. The results of the study show that the application of the Whole language approach in teaching early childhood literacy has significant benefits. Children are actively involved in reading and writing activities, they show a high interest in literacy, and improve overall language comprehension. In addition, children also develop speaking and listening skills through interactions with teachers and peers. This research provides insight into the effectiveness of the Whole language approach in the context of teaching early childhood literacy. The practical implication of this research is the need to apply the Whole language approach in the early childhood education curriculum to improve literacy and holistic language development.